الاقتصاد السياسي للدولة الريعية ومأزق الخيار الديمقراطي في ليبيا (Economic studies journal, 2019)
This study seeks to examine the nature of relationship between democratic choice and the one-sided rentier economy which would deepen the culture of wealth consumption rather than produce it, and enhances the dependency of society to the State and reduces opportunities for democratic transition. The dependency of rentier state on oil revenues instead of taxes saves it from the accountability of its citizens and promotes its independence politically. This type of countries adopts a policy of distribution that leads to the exclusion of citizens from the political sphere, nonetheless it makes them rely and obey it, and therefore does not pay attention to any internal or external pressures for political participation. The dominance of the rentier economy leads to the emergence of an unaccountable political system, where the rentier economy generates a political and social class that works with its gains and prestige to impede the shift to diversification of the economy and thus impede the democratic transition.
Keywords: Political Economy; Rentier Economy; Rentier State; Dilemma of Democracy